A = -x² - 6x + 1
= -(x² + 6x - 1)
= -(x² + 6x + 9 - 10)
= -[(x + 3)² - 10]
= -(x + 3)² + 10
Do (x + 3)² ≥ 0 với mọi x ∈ R
⇒ -(x + 3)² ≤ 0 với mọi x ∈ R
⇒ -(x + 3)² + 10 ≤ 10 với mọi x ∈ R
Vậy GTLN của A là 10 khi x = -3
\(A=-x^2-6x+1\)
\(A=-\left(x^2+6x-1\right)\)
\(A=-\left(x^2+6x+9-10\right)\)
\(A=-\left(x^2+2\cdot x\cdot3+3^2\right)+10\)
\(A=-\left(x+3\right)^2+10\)
Có: \(\left(x+3\right)^2\ge0\forall x\Rightarrow-\left(x+3\right)^2\le0\)
\(\Rightarrow-\left(x+3\right)^2+10\le10\)
\(\Rightarrow A\le10\)
Dấu "=" xảy ra khi \(\left(x+3\right)^2=0\Leftrightarrow x+3=0\)
\(\Leftrightarrow x=-3\)
Vậy: \(A_{min}=10\Leftrightarrow x=-3\)